PERBANDINGAN HASIL BELAJAR FISIKA MATERI POKOK VEKTOR DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) DAN JIGSAW KELAS X MAN SIPIROK - Mutiara Siagian (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2023)
The aim of this research was to know whether there was any significant difference between using Teams Games Tournament (TGT) model and Jigsaw model in vektor subject at tenth grade students of MAN Sipirok. The approach of this research was experimental method. Sample of this research was 63 students. Data was collected by using test and observation. Based on descriptive analysis, the average of using TGT model was 3.75, it was categorized “very good” while the average of using Jigsaw model was 3.66, it was categorized “very good”. The average of vektor subject by using TGT model was 85, it was categorized “good” while the average of vektor subject by using Jigsaw model was 78.33, it was categorized “enough”. Based on statistic inferential analysis by ttest formula to test hypothesis, it could be gotten tcount = 3.182 and ttable = 1.670 at error level 5%. It can be seen that tcount is greater than ttable (3.182<1.670). It means alternative hypothesis was accepted. In the other words, there was any significant difference between using Teams Games Tournament (TGT) model and Jigsaw model in vektor subject at tenth grade students of MAN Sipirok.